Dechlorination of 2, 4‐dichlorophenoxyacetic acid using biochar‐supported nano‐palladium/iron: Preparation, characterization, and influencing factors. (21st September 2020) - Zhou, Hongyi; Huang, Ning; Zhao, Yongkang; Baig, Shams Ali; Xiang, Junchao
Abstract : In the present study, peanut shell, a green waste raw material, was used to prepare biochar (BC) and to obtain BC‐supported nano‐palladium/iron (BC‐nPd/Fe) composites for removing 2, 4‐dichlorophenoxyacetic acid (2, 4‐D) from water. Characterization analysis demonstrated that nPd/Fe particles were well dispersed on the BC surface with weakened magnetic properties. The average particle diameter and specific surface area of nPd/Fe were 101.3 nm and 6.7 m 2 g −1, whereas the corresponding values of the BC‐nPd/Fe materials were 88.8 nm and 14.8 m 2 g −1, respectively. Several factors were found to influence the dechlorination of 2, 4‐D, including the weight ratio of BC to Fe, Pd loading ratio, initial solution pH, 2, 4‐D concentration, and reaction temperature. Dechlorination results indicated that the 2, 4‐D removal and phenoxyacetic acid (PA) generation rates were 44.1% and 20.1%, respectively, in the nPd/Fe system, and 100.0% and 92.1%, respectively, in the BC‐nPd/Fe system. The dechlorination of 2, 4‐D was well described by the pseudo‐first‐order kinetic model ( R 2 > 0.97), and the observed rate constants k obs were 0.0042 min (nPd/Fe) and 0.0578 min (BC‐nPd/Fe), respectively. The reaction mechanism indicated that the dechlorination hydrogenation was the main process to remove 2, 4‐D from water in the BC‐nPd/Fe system. In addition, BC inhibited the formation of a passivation layer on the particle surface during the reaction, thus maintaining the high reactivity of BC‐nPd/Fe. The easy preparation technique, high 2, 4‐D dechlorination capacity, and mild reaction conditions suggest that BC‐nPd/Fe may be a promising alternative composite to remove 2, 4‐D from water. Abstract : When the supporting material biochar (BC) was introduced, the nano‐palladium/iron (nPd/Fe) particles with smaller size were dispersed on the surface of BC. Compared with nPd/Fe, the dechlorination efficiency and k obs of 2, 4‐dichlorophenoxyacetic acid (2, 4‐D) by BC‐supported nPd/Fe (BC‐nPd/Fe) were significantly increased, which mainly due to the passivation layer formation was inhibited during the reaction.